2013
DOI: 10.1038/nrmicro2992
|View full text |Cite
|
Sign up to set email alerts
|

A cornucopia of human polyomaviruses

Abstract: During the past 6 years, focused virus hunting has led to the discovery of nine new human polyomaviruses, including Merkel cell polyomavirus, which has been linked to Merkel cell carcinoma, a lethal skin cell cancer. The discovery of so many new and highly divergent human polyomaviruses raises key questions regarding their evolution, tropism, latency, reactivation, immune evasion and contribution to disease. This Review describes the similarities and differences among the new human polyomaviruses and discusses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
313
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(321 citation statements)
references
References 161 publications
(141 reference statements)
7
313
0
1
Order By: Relevance
“…However, only the Merkel cell polyomavirus has been linked to Merkel cell carcinoma and none of the others have been associated to cancer so far. [34][35][36] We found that the risk of CIN3/CIS and ICC linearly increased with increasing number of STIs the woman had had, including HPV, CT, and HHV-2. We do not know whether exposure to CT and/or HHV-2 truly contribute with HPV in ICC causation, or different STIs tend to cluster because of the common transmission route (reflecting thus a high-risk sexual behavior by the subject or her sexual partners), or whether this increase in the risk of CC reflect a decreased immunologic response to clear STIs.…”
Section: Epidemiologymentioning
confidence: 72%
“…However, only the Merkel cell polyomavirus has been linked to Merkel cell carcinoma and none of the others have been associated to cancer so far. [34][35][36] We found that the risk of CIN3/CIS and ICC linearly increased with increasing number of STIs the woman had had, including HPV, CT, and HHV-2. We do not know whether exposure to CT and/or HHV-2 truly contribute with HPV in ICC causation, or different STIs tend to cluster because of the common transmission route (reflecting thus a high-risk sexual behavior by the subject or her sexual partners), or whether this increase in the risk of CC reflect a decreased immunologic response to clear STIs.…”
Section: Epidemiologymentioning
confidence: 72%
“…For example, infections caused by the human BK, JC, and Merkel cell PyVs can lead to PyV-associated nephropathy, progressive multifocal leukoencephalopathy, and Merkel cell carcinoma, respectively (1,2). Simian virus 40 (SV40) traditionally has been used as a model for studying this virus family and has structural and genetic similarities to human PyVs.…”
mentioning
confidence: 99%
“…HPyV seroprevalence data obtained using the major capsid protein Vp1 as pentamers or virus-like particles indicate that HPyVs infect 50% to 90% of the general human population without known specific signs or symptoms of disease (2)(3)(4)(5)(6)(7). As information about the virology and pathology of the 13 human PyVs is only emerging (8,9), we focused on BK polyomavirus (BKPyV) as a model (10).…”
mentioning
confidence: 99%